Sistem Informasi Manajemen Kepangkatan Jabatan Fungsional Online Polmanbabel - Ammar Naufal Ammar (Repository STMIK Prabumulih, 2022)
Functional positions or academic positions are an acknowledgment of trust in performance, integrity, and responsibility in carrying out tasks, as well as lecturer etiquette in carrying out the tri dharma of higher education. Each functional position has certain qualifications and criteria, duties, responsibilities, and authorities. To be able to lift a functional position, lecturers must collect a number of credit points. The credit figure is an accumulation of dharma elements which include the main tri-high elements consisting of the implementation of education and teaching, research implementation, and community service implementation as well as other supporting elements. The value of the proposed credit can be reduced in accordance with the provisions of the reviewer. The number of requirements in the submission of functional positions and the long submission time as well as the submission of functional position submissions that are still done manually make the process of applying for functional positions at the Bangka Belitung State Manufacturing Polytechnic ineffective. Therefore, ordering a web-based lecturer information system is expected to be used to facilitate the process of applying for functional positions at the Bangka Belitung State Manufacturing Polytechnic.